Evaluation of Reinventing Government Policy on Financial Management Performance of Education Public Service Agencies on Ministry of Transportation - Eka Sari Prihartanti; Muhammad Zilal Hamzah; Eleonora Sofilda (Proceedings, 2022)
The objectives of this research are (1) to analyze and assess the level of interest or expectations of the government, the management of the Public Service Agency (PSA), and stakeholders on the implementation of bureaucratic entrepreneurship, and (2) to analyze and assess the perception of the government, the management of the Public Service Agency, and stakeholders on current problems. This research uses a combination of quantitative and qualitative descriptive research approaches, where the data are sourced from primary data and secondary data through focus group discussions and processed with the NVivo program. The object of this research is 23 work units within the patterns of the financial management section of the PSA at the Ministry of Transportation.